Answer:
Explanations:
Let the coordinates of the focus(-3, 0) be:
x₁ = -3, y₁ = 0
Let the coordinates of the focus(3, 0) be:
x₂ = 3, y ₂ = 0
Let the coordinates of point(7, 0) be:
x₃ = 7, y₃ = 0
Let the distance between the Focus(-3, 0) and (7, 0) be d₁
![\begin{gathered} d_1=\text{ }\sqrt[]{(x_3-x_1)^2+(y_3-y_1)^2} \\ d_1=\text{ }\sqrt[]{(7-(-3))^2+(0-0)^2} \\ d_1=\text{ }\sqrt[]{10^2} \\ d_1=\text{ 10} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/awf9lqg5ebgisi22gjv4qda9oxq3zz89ve.png)
Let the distance between the Focus (3, 0) and (7, 0) be d₂
![undefined]()